Whistle lower-better late than never - Arjun Srinivasan; Mahadevan Sivaramakrishnan; Pattabhi Raman R Vallandramam; Pavan Yadav (Lung India, 2016)
16 years old boy with childhood history of chronic respiratory symptoms requiring several admissions presented with recent worsening of symptoms. Chest x-ray showed left lower lobe collapse and flexible bronchoscopy revealed stenosis of left main bronchus. Foreign body was seen beyond the stenosis, which was removed after dilatation of narrowed bronchus under general anesthesia using rigid bronchoscopy. Patient′s father gave a history of aspiration of whistle 14 years ago, which had then been removed. Patient is now free of symptoms after removal of foreign body.